The Painting Creation for Furniture Decoration Named “Mai Leuay” (Ivy) - Jandahong, Ponsawan (Chophayom Journal, 2020)
This painting creation for furniture decoration has named “Mai Leuay” (ivy). Concept of this painting is natural ivy that has various beauties included bud flower, blooming flower, falling flower and other parts of ivy such as Petrea volubilis, Drunken sailor and Bengal clock vine. All relative information and something that making the idea, feeling and imagine bring to various beautiful painting. The painting has been to blend with concept its cause to be a painting for wood furniture decoration named “Mai Leuay” series. It is showing the beauty of ivy that is the inspiration to making this painting. This painting will increase the beauty and value to the furniture. The look of painting focus on the blending of imagination and nature that important part of beauty. This painting has technique, method, process from data analysis until the process completed according to the goal. Keywords: Panting creation, Decoration, Wood furniture, Ivy